Effect of Collective Bargaining on Industrial Disputes Management - Egesa Simon Ukokhe; Olouch Mercy Florah (European Scientific Journal, ESJ, 2022)
The industrial conflict appears to be a major problem hindering development in developing countries in general. It has been established that industrial disputes cause economic losses to organizations and poor relationships among employees and employers. Although conflict in an organization is inevitable, it should be understood that disputes between employees and employers must be reduced through mutually agreed mechanisms to a reasonable level that enables the creativity and performance of employees and the organization at large. This independent study paper seeks to review the effect of collective bargaining on industrial dispute management. The study will be guided by pluralism theory, Unitarian theory, systems theory, and human relations theory. The study concluded that collective bargaining agreement, joint consultation, and grievance handling are key tenets of industrial dispute management.  The management and employee must embrace dispute management in totality to enhance industrial harmony, foster organizational performance, and enhance employee trust in management. It is recommended that all parties should respect the rights of each party in negotiation and that the agreement reached is documented and cited as the point of reference in resolving disputes. The study also recommends that management should strive to allow a give and take position while resolving conflicts, provide a grievance handling process that is timely and fair, involve both parties, and ensure that grievance capturing mechanism is readily available to all parties. The study further recommends that joint consultation committees, unions, and management should coexist to resolve any dispute which arises. In mutual coexistence environment, the organization is able to tap into the stock of ideas, which are available within the organization.